Integration of Islamic Politics and Economics: A Solution for Sustainable Development in Indonesia - Rizki Ardiansyah; Kurrotul Uyun; Zaenab (Al-Abqori: Journal of Islamic Thought Studies, 2025)
This study aims to examine how the integration of Islamic politics and economics can be an effective solution to achieve sustainable development. Islamic principles, such as justice, balance, social responsibility, and welfare, are used as the basis for forming a political and economic framework that is oriented towards the welfare of the people. This study uses a qualitative approach using policy analysis to examine the perspectives of Islamic politics and economics in creating an inclusive, just, and sustainable environment in Indonesia.